2010
DOI: 10.1590/s0103-50532010000700019
|View full text |Cite
|
Sign up to set email alerts
|

Substituted tridentate pyrazolyl ligands for chromium and nickel-catalyzed ethylene oligomerization reactions: effect of auxiliary ligand on activity and selectivity

Abstract: . The presence of this auxiliary ligand has a strong impact on the selectivity towards the production of a-olefins, decreasing substantially the amount of 1-butene with a concominat increase of the 2-butene fractions. Attempts to crystallize the nickel complex 3 afforded the tetrametallic [{(L)(μ 3 -Cl)NiCl} 4 ] (4, L = 1-anilinomethyl-3,5-dimethylpyrazole) which was characterized by X-ray diffraction analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…13 The structures of two related complexes were only suggested on the basis of spectroscopic data, 14 whereas [Ni II Cl 2 {N-benzyl-1-(3,5-dimethyl-1H-pyrazol-1-yl)methanamine}] 4 , which belongs to this family, has been obtained in a non-measurable yield. 15 It appears that the only other Ni 4 cubane-type complex with triply-bridging halides is [Ni 4 F 4 {bis( pyrazolyl)-sulfan} 4 (µ-FAsF 4 F) 2 ](AsF 6 ) 2 • 4SO 2 , which does not however correspond to the general formulation [NiX 2 Z 2 ] 4 . 16 Mononuclear square planar (type A), 17 tetrahedral (type B) 18 and dinuclear structures [NiX 2 Z 2 ] 2 (types C and D in Scheme 4) 19 are common for Ni(II) complexes, whereas "tetramerization" of a mononuclear building block remains rarely observed.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…13 The structures of two related complexes were only suggested on the basis of spectroscopic data, 14 whereas [Ni II Cl 2 {N-benzyl-1-(3,5-dimethyl-1H-pyrazol-1-yl)methanamine}] 4 , which belongs to this family, has been obtained in a non-measurable yield. 15 It appears that the only other Ni 4 cubane-type complex with triply-bridging halides is [Ni 4 F 4 {bis( pyrazolyl)-sulfan} 4 (µ-FAsF 4 F) 2 ](AsF 6 ) 2 • 4SO 2 , which does not however correspond to the general formulation [NiX 2 Z 2 ] 4 . 16 Mononuclear square planar (type A), 17 tetrahedral (type B) 18 and dinuclear structures [NiX 2 Z 2 ] 2 (types C and D in Scheme 4) 19 are common for Ni(II) complexes, whereas "tetramerization" of a mononuclear building block remains rarely observed.…”
Section: Dalton Transactions Papermentioning
confidence: 99%
“…On comparing these results with those based on MAO‐activated chromium complexes containing bis(pyrazolyl) ligands, [ 48,51 ] it is clear that the presence of a bridge soft S ‐donor atom positively affects the catalytic performance of these chromium complexes. However, the formation of more strained 5‐membered‐ring chromium complexes afford catalytic systems with lower activities.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies by our group and others have shown that pyrazolyl-based metal complexes are efficient catalysts for oligomerization of ethylene producing mostly oligomers with high selectively for α-olefins. [46][47][48][49][50][51][52][53][54][55][56] In particular, we have reported chromium complexes based on tridentate pyrazolyl ligands as highly selective and active systems for ethylene oligomerization when activated with MAO. [48,51,56] As an extension of our continuous interest in this field, we herein report the synthesis, characterization, and catalytic performance in oligomerization and polymerization of ethylene of a new set of 5-membered Cr (III) complexes supported by bis(pyrazolyl)thioether/ amine ligands containing pendant O-and N-donor groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 17–81 ] In particular, chromium catalysts stabilized by pyrazolyl‐based tridentate ligands have been successfully synthetized and their catalytic application in ethylene oligomerization explored in details. [ 51,81–91 ] Selected examples are presented in Chart 1. For instance, Tosoh Corporation reported chromium complex bearing tris(3,5‐dimethyl‐1‐pyrazolyl)methane ligand that, once activated with methylalumoxane (MAO), generate highly active oligomerization/polymerization species 526.0 x 10 3 (mol ethylene) (mol Cr) −1 ·h −1 with selectivity for 1‐hexene >99.5%.…”
Section: Introductionmentioning
confidence: 99%